Kinetic analysis of multi‐resolution hyperpolarized 13C human brain MRI to study cerebral metabolism. Issue 5 (26th June 2022) - Hu, Jasmine Y.; Kim, Yaewon; Autry, Adam W.; Frost, Mary M.; Bok, Robert A.; Villanueva‐Meyer, Javier E.; Xu, Duan; Li, Yan; Larson, Peder E. Z.; Vigneron, Daniel B.; Gordon, Jeremy W.
Abstract : Purpose: To investigate multi‐resolution hyperpolarized (HP) 13 C pyruvate MRI for measuring kinetic conversion rates in the human brain. Methods: HP [1‐ 13 C]pyruvate MRI was acquired in 6 subjects with a multi‐resolution EPI sequence at 7.5 × 7.5 mm 2 resolution for pyruvate and 15 × 15 mm 2 resolution for lactate and bicarbonate. With the same lactate data, 2 quantitative maps of pyruvate‐to‐lactate conversion (kPL ) maps were generated: 1 using 7.5 × 7.5 mm 2 resolution pyruvate data and the other using synthetic 15 × 15 mm 2 resolution pyruvate data to simulate a standard constant resolution acquisition. To examine local kPL values, 4 voxels were manually selected in each study representing brain tissue near arteries, brain tissue near veins, white matter, and gray matter. Results: High resolution 7.5 × 7.5 mm 2 pyruvate images increased the spatial delineation of brain structures and decreased partial volume effects compared to coarser resolution 15 × 15 mm 2 pyruvate images. Voxels near arteries, veins and in white matter exhibited higher calculated kPL for multi‐resolution images. Conclusion: Acquiring HP 13 C pyruvate metabolic data with a multi‐resolution approach minimized partial volume effects from vascular pyruvate signals while maintaining the SNR of downstream metabolites. Higher resolution pyruvate images for kinetic fitting resulted in increased kinetic rate values, particularly around the superior sagittal sinus and cerebral arteries, by reducing extracellular pyruvate signal contributions from adjacent blood vessels. This HP 13 C study showed that acquiring pyruvate with finer resolution improved the quantification of kinetic rates throughout the human brain.